The Role of Internal and External Environment For The Sustainability of MSMEs - Vinsensius Widdy Tri Prasetyo; Lena Ellitan (CV. ULIL ALBAB CORP, 2023)
The existence of MSMEs has become a support for the recovery of the national economy after Indonesia was hit by a crisis during the pandemic. The role of MSMEs is very large in driving Indonesia's economic activities, both as primary and secondary sources of income. MSMEs in Indonesia have an important contribution as a support for the economy. The main driver of the economy in Indonesia so far has basically been the MSME sector. Apart from playing a role in national economic growth and employment, MSMEs also play a role in the distribution of development results and are a driving force for the growth of national economic activity. The existence of MSMEs is very helpful for people who have no income or who don't have a job (unemployed), where people can open small businesses in their surroundings so that they can earn income, even though this small one is very helpful for their daily needs. To support the survival of SMEs, it is necessary to provide support and facilities for their development, especially among poor families and/or in underdeveloped areas and pockets of poverty. This research is a literature review research that discusses the factors studied in research related to the analysis of the internal and external environment of an industry or business. The object of this research is a research article that identifies internal and external environmental factors in MSMEs/UKM in Indonesia in the year of publication 2016-2023. The process of searching for articles used as literature through the literature review method is a systematic, explicit, reproducible method for identifying, evaluating and synthesizing research works that have been produced by researchers. Every business is always faced with an ever-changing environment. This condition is not possible without an adjustment process to existing internal conditions. The external and internal environment is the key to the survival of MSMEs. This paper discusses the role of the internal and external environment in ensuring the survival of MSMEs.